NTR1 is involved in heat stress tolerance through mediating expression regulation and alternative splicing of heat stress genes in Arabidopsis - He, Lei; Wu, Qi; Jin, Ye; Fan, Ye; Shi, Huazhong; Wang, Yizhong; Yang, Wannian (Frontiers in Plant Science, 2023)
As a common adverse environmental factor, heat stress (HS) not only drastically changes the plant transcriptome at the transcription level but also increases alternative splicing (AS), especially intron retention (IR) events. However, the exact mechanisms are not yet well understood. Here, we reported that NTC-related protein 1 (NTR1), which acts as an accessory component for spliceosome disassembly, is necessary for this process. The mutants of NTR1, both the T-DNA insertion and the point mutation identified through ethyl methanesulfonate (EMS) mutagenesis screening, are vulnerable to HS, indicating that NTR1 is essential for plant HS tolerance. At the molecular level, genes of response to heat and response to temperature stimulus are highly enriched among those of heat-induced but less-expressed ntr1 mutants. Moreover, a large portion of HS response (HSR) genes such as heat shock transcription factors (HSFs) and heat shock proteins (HSPs) are less induced by heat treatment, and more AS events, especially IR events, were found in heat-treated ntr1 mutants. Furthermore, HS suppressed the expression of NTR1 and NTR1-associated complex components. Thus, it is very likely that upon HS, the plant reduces the expression of the NTR1-associated complex to fulfill the fast demands for transcription of HSR genes such as HSFs and HSPs, which in turn results in the accumulation of improperly spliced especially IR products and eventually causes harm to plants.